Soot formation and effect on engine oils - S. V. Pashukevich (Вестник СибАДИ, 2023)
Introduction. During the combustion of diesel fuel in a diesel engine with an increased fuel supply, as a result of its incomplete combustion, soot particles are formed, which are either released into the atmosphere or inevitably enter the engine oil. Soot, polluting the engine oil, causes a change in its quality indicators. Soot is very small particles formed by a complex reaction mechanism in the flame of a fuel-rich region during the combustion of hydrocarbons in the absence of air, mainly consisting of a mixture of amorphous carbon and organic matter.Materials and methods. This paper presents the results of a literary review aimed at studying the ways of soot occurrence during the operation of diesel engines, its effect. The mechanical properties of diesel soot are also discussed on the surfaces of friction pairs and engine components.Conclusions. The soot content in engine oil will increase sharply in engines with exhaust gas recirculation, which leads to an increase in temperature in the friction zones and viscosity of the lubricant, as well as to the formation of deposits on hot parts. These processes occur due to the discharge in the crankcase space and the intensification of the intake of gases from the combustion chamber. Oil change intervals should be monitored at an increased rate of soot entering the engine oil.Scope of the study / opportunity. This type of study will help determine the causes of soot in a diesel engine, understand the consequences of using engine oil contaminated with soot particles.Originality / value. The conducted research can be the basis for the development of recommendations for improving the maintenance of internal combustion engines for enterprises that have cars with diesel engines at their disposal in order to increase the resource of power units and reduce operating costs.